2010
DOI: 10.1001/archneurol.2009.335
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Levetiracetam in Patients With Glioma

Abstract: To evaluate the efficacy and safety of levetiracetam in the management of epilepsy in patients with glioma.Design: A prospective study in hospitalized patients with a new diagnosis of glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 23 publications
(34 reference statements)
1
52
2
3
Order By: Relevance
“…Additionally, there was no decline in overall quality of life, overall health or cognitive function, as assessed by EORTC quality of life questionnaire and MMST ( Figure 1). This corroborates the recent results on safety and tolerability from retrospective or smaller studies applying LEV in brain tumor patients or in patients undergoing any supratentorial neurosurgery (6,9,10,18,22,23,30).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, there was no decline in overall quality of life, overall health or cognitive function, as assessed by EORTC quality of life questionnaire and MMST ( Figure 1). This corroborates the recent results on safety and tolerability from retrospective or smaller studies applying LEV in brain tumor patients or in patients undergoing any supratentorial neurosurgery (6,9,10,18,22,23,30).…”
Section: Discussionsupporting
confidence: 89%
“…LEV was the first new AED with an intravenous formulation being available (1,16,17,21). Therefore, LEV might be a first choice for the treatment of brain tumorrelated epilepsy (3,18,23 …”
Section: Introductionmentioning
confidence: 99%
“…In a uncontrolled prospective study, LEV was shown to be well tolerated and provided a good seizure improvement in 17 patients with BTE (Usery, Michael et al, 2009). Further studies confirmed the good profile of LEV in BTE Rosati, Buttolo et al ;Maschio, Albani et al 2006;Newton, Goldlust et al 2006) and metastatic brain tumor epilepsy Newton, Dalton et al 2007). Several experts recommend use of LEV as first monotherapy in BTE Vecht and Wilms ;Vecht and van Breemen 2006;van Breemen, Rijsman et al 2009), although others still suggest valproic acid, lamotrigine and topiramate as first choice treatments (van Breemen, Wilms et al 2007).…”
Section: -5 Antiepileptic Pharmacotherapymentioning
confidence: 57%
“…Levetiracetam-Overall side-effects of levetiracetam in EBT are seen in 5-10% of patients, often of psychiatric nature, including psychosis, depression, and aggressive behavior (Merrell et al, 2010b;Rosati et al, 2010;Maschio et al, 2011b;Rossetti et al, 2014). On the other hand, levetiracetam shows improvement in cognitive functioning in both EBT and general epilepsy (Helmstaedter and Witt, 2008;de Groot et al, 2013).…”
Section: Adverse Effects Of Aedsmentioning
confidence: 99%